Biomaterial implants in the treatment of oncology: a review - Maanvizhi, Saba; Ramamurthy, Vijayakumar Arumugam; Velan, Athithan; Thangaraju, Pugazhenthan (International Journal of Basic & Clinical Pharmacology, 2021)
In globally, cancer is a second leading disease next to cardiovascular diseases in non-communicable diseases, which affect the all ages, sex, social status, ethnicity and primary cause of illness related death. Traditionally, systemic delivery drug systems like chemotherapy via oral capsule, injections of nanoparticles/micro particles, immunotherapy and others, which can inhibit or halt the progression of tumors. The short half-life of drugs which cannot achieve the targeted dose level to the tumor site and not able to target desired cell and commonly produces the organ toxicity. Recently, researchers have been attempting to direct delivery agents for cancer therapy. One of the best methods is a local therapy system, which deliver the drug directly via implantable procedure and it’s achieved the maximum concentration of the desire drug at the tumor site, non-target systemic exposure and minimize the organ toxicity to the patients. Biomaterial implants are widely used in the local concurrent delivery of chemotherapy and anti-angiogenic agents, local delivery of poly-chemotherapy, gene therapy as an alternative to drug delivery, scaffolds for cancer immunotherapy and polymer-based composites of drug molecules. There are different types of polymers like poly anhydride poly [bis (p-carboxy-phenoxy) propane-sebacic acid] copolymer [p(CPP:SA)], fatty acid dimer-sebacic acid copolymer (FAD-SA), poly (lactic-co-glycolic acid) copolymer (PLGA), poly (ε-caprolactone) (PCL), poly (glycerol monostearate-co-caprolactone), alginate and silica, used in successively cancer therapy. In order to minimize the risk of unwanted side effect of different types of biomaterials implants, it’s biocompatible to reduce the ability to elicit the inflammatory effect to the implanted area or the site. Therefore, the key role of choosing the appropriate and biocompatible implants to particular therapy is an indispensable. This should be validated with respect to risk benefit ratio in case of cancers. Biomaterial based implant local delivery systems provide more versatile and tailorable approach to against treatment of different types of the cancer.